HUBUNGAN FAKTOR INDIVIDU, DURASI KERJA, DAN TINGKAT RISIKO ERGONOMI TERHADAP KEJADIAN MUSCULOSKELETAL DISORDERS PADA PENENUN SONGKET PANDAI SIKEK - Zahra Halfa' Badriyyah; Yuliani Setyaningsih; Ekawati Ekawati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2021)
Musculoskeletal Disorders (MSDs) are disorders due to injury to muscles, tendons, ligaments, nerves, cartilage, bones, or blood vessels ranging from complaints of mild to very severe pain. This study aims to analyze individual factors and occupational factors related to the incidence of Musculoskeletal Disorders in songket weavers in Nagari Pandai Sikek, West Sumatra. This research is an analytic observational research with a cross sectional study design. The research sample was songket weavers totaling 70 people. Chi-square analysis showed that age (p-value = 0.005), years of service (p-value = 0.008), history of disease (p-value = 0.001), work duration (p-value = 0.000), and level of ergonomics risk (p-value = 0.002) had significant correlation with Musculoskeletal Disorders. This study also showed that the complaints most felt by weavers were in the waist (97.1%), back (94.3%), right shoulder (78.6%), bottom (77.1%), and left shoulder (77.1%).